The Crime of Human Trafficking from the Perspective of National and International Law - Daffa Jati Nugroho; Yusuf Saefudin (Proceedings Series on Social Sciences & Humanities, 2023)
Human trafficking is a form of abuse that violates human dignity. Human trafficking in the form of organised crime networks is increasing both domestically and internationally. This organised crime makes it difficult for governments to deal with it and protect its victims. Bloomsbury University refers to human trafficking as "human trafficking", which is "the illegal process of finding and mistreating people for unpaid and often unpleasant labour in settings with no rights defined as the act. How is the legal regulation of human trafficking crimes nationally and internationally and how is the legal protection for victims of these crimes? The method used in writing this research is an analytical approach with legal concepts or statutory approach. The results of the research show that although the regulation on human trafficking is contained in international instruments such as the Palermo Protocol, the domestic regulation in Law Number 21 Year 2007 on Crime Eradication does not allow the trade of human organs by Indonesians. However, if the organ can be used to save the life of another person, for example by transplantation, there will be additional legal requirements for human organ transplantation. For the regulation of human organ trafficking in Indonesia, Law No. 21 Year 2007 on the Eradication of the Criminal Offence of Trafficking in Persons. Currently, the form of protection for victims of human trafficking and human trafficking offences is to punish the perpetrators legally and fulfil the needs of the victims.